EASTERN ADRIATIC CITIES AND THEIR ROLE IN VENETIAN (LONG-DISTANCE) COMMERCIAL ACTIVITIES DURING THE 13TH AND THE FIRST HALF OF THE 14TH CENTURY – AN OVERVIEW (Review of Croatian History, 2022)
The main strategy was to maintain the sea route from the northernmost point of the Adriatic to the Levant, and to introduce the necessary legal, commercial, and administrative practices modelled upon its own. During the 13th and 14th centuries Venice worked on gaining military and economic control over the Eastern Adriatic and “prepared the ground” for its later long dominance in that area. In this period, from Venetian perspective, the cities were primarily strategic and exchange points – and were increasingly perceived as the natural hub of connections between the Mediterranean and Central Europe or the West and the Levant. The infrastructures that supported the Venetian long-distance trade in the 13th and 14th centuries were related to security, equipment, and the possibility of transit, as well as supplying enough manpower on the way.